Pengaruh Kualitas Pelayanan Eceran (Retail Marketing Mix Application) terhadap Kepuasan Konsumen - Amandin Amandin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Given how important the role of service quality is for the life of an organization or company to try to increase its potential, so that the quality and quantity of these services can compete or at least be able to keep up with the pace of competition in the business world. This study aims to determine the Effect of Retail Service Quality (Retail Marketing Mix Application) on Consumer Satisfaction in Alfamart Jl. Raya Palembang-Prabumulih, Gelumbang District, Muara Enim Regency. The method used in this study is a survey method. The data collected consists of primary data and secondary data. Primary data obtained through the interview method that is equipped with a questionnaire that has been prepared. Secondary data were obtained from related companies, as well as several library sources in the form of journals and books relating to this research. And the research design used is causal associative design. In this research, what will be analyzed is the effect of service quality consisting of reliability, responsiveness, assurance, empathy, tangible. The results showed the calculation of the coefficient of determination (R2) was used to determine what percentage of the dependent variable variation could be explained by the variation of the independent variables. From the SPSS output display, the summary model of customer satisfaction is influenced or explained by variations in the five dimensions of service quality, namely physical evidence, reliability, responsiveness, assurance, care. Therefore it can be concluded that the retail marketing mix delivered well by the company can increase customer satisfaction. Keywords: Service Quality, Consumer Satisfaction